Paternal postnatal depressive symptoms, infant sleeping and feeding behaviors, and rigid parental regulation: a correlational study. (December 2014) - Cockshaw, Wendell D; Muscat, Tracey; Obst, Patricia L; Thorpe, Karen
Abstract Paternal postnatal depression (PND) is now recognized as a serious and prevalent problem, associated with poorer well-being and functioning of all family members. Aspects of infant temperament, sleeping and feeding perceived by parents as problematic are associated with maternal PND, however, less is known about paternal PND. This study investigated depressive symptoms (Edinburgh postnatal depression scale (EPDS)) in 219 fathers of infants aged from 1 to 24 weeks (median 7.0 weeks). Infant predictor variables were sleeping problems, feeding problems and both mother and father reported temperament. Control variables were partner's support, other support and life events. Rigidity of parenting beliefs regarding infant regulation was also measured as a potential moderating factor. Infant feeding difficulties were associated with paternal depressive symptoms, subsuming the variance associated with both sleep problems and temperament. This relationship was not moderated by regulation beliefs. It was concluded that infant feeding is important to fathers. Fathers of infants with feeding difficulties may not be able to fulfill their idealized construction of involved fatherhood. Role incongruence may have an etiological role in paternal PND.